(untitled) (Proceeding of SINERGY, 2026)
This article explores the Spice conduit as a global cultural conduit, how it shaped regional identity in Maritime Southeast Asia, and how it is being reinterpreted as a soft power pillar. Southeast Asia was historically integrated into early global economic and cultural systems through the Spice Route, which linked the archipelagic areas through extensive networks of maritime movement, trade, and cultural exchange. The Spice Route was more than just a commercial route; it was a complex social and cultural environment where power dynamics, interaction, and hybridity shaped identities. This study uses a qualitative historical-critical method to examine how memories of the Spice Route are mobilized and remade in modern cultural diplomacy, drawing on maritime historiography, regional identity theories, and the idea of soft power. The results demonstrate that whereas narratives of marine cosmopolitanism and regional connection have been reinforced by the rebirth of the Spice Route, its current use is frequently influenced by specific national goals. Because of this, shared heritage is often divided into incomplete narratives that prioritize symbolic appeal while ignoring local experiences, colonial violence, and historical injustices.The paper makes the case that the Spice Route offers a framework for interaction through which identities are constantly negotiated rather than naturally creating a cohesive regional identity. Its legitimacy as a soft power source rests on regional cooperation, historical accuracy, and local community inclusivity. In the absence of these prerequisites, the Spice Route runs the risk of becoming little more than cultural branding rather than a useful diplomatic tool. By emphasizing the moral and political difficulties in turning historical memory into modern soft power, the study adds to conversations on maritime heritage, cultural diplomacy, and regional identity in Southeast Asia.